How do treatment times impact on functional outcome in stroke patients undergoing thrombectomy in Germany? Results from the German Stroke Registry. Issue 8 (October 2021) - Herm, Juliane; Schlemm, Ludwig; Siebert, Eberhard; Bohner, Georg; Alegiani, Anna C; Petzold, Gabor C; Pfeilschifter, Waltrud; Tiedt, Steffen; Kellert, Lars; Endres, Mattias; Nolte, Christian H
Background: Functional outcome post-stroke depends on time to recanalization. Effect of in-hospital delay may differ in patients directly admitted to a comprehensive stroke center and patients transferred via a primary stroke center. We analyzed the current door-to-groin time in Germany and explored its effect on functional outcome in a real-world setting. Methods: Data were collected in 25 stroke centers in the German Stroke Registry-Endovascular Treatment a prospective, multicenter, observational registry study including stroke patients with large vessel occlusion. Functional outcome was assessed at three months by modified Rankin Scale. Association of door-to-groin time with outcome was calculated using binary logistic regression models. Results: Out of 4340 patients, 56% were treated primarily in a comprehensive stroke center and 44% in a primary stroke center and then transferred to a comprehensive stroke center ("drip-and-ship" concept). Median onset-to-arrival at comprehensive stroke center time and door-to-groin time were 103 and 79 min in comprehensive stroke center patients and 225 and 44 min in primary stroke center patients. The odds ratio for poor functional outcome per hour of onset-to-arrival-at comprehensive stroke center time was 1.03 (95%CI 1.01–1.05) in comprehensive stroke center patients and 1.06 (95%CI 1.03–1.09) in primary stroke center patients. The odds ratio for poor functional outcome per hour of door-to-groin time was 1.30 (95%CI 1.16–1.46) in comprehensive stroke center patients and 1.04 (95%CI 0.89–1.21) in primary stroke center patients. Longer door-to-groin time in comprehensive stroke center patients was associated with admission on weekends (odds ratio 1.61; 95%CI 1.37–1.97) and during night time (odds ratio 1.52; 95%CI 1.27–1.82) and use of intravenous thrombolysis (odds ratio 1.28; 95%CI 1.08–1.50). Conclusion: Door-to-groin time was especially relevant for outcome of comprehensive stroke center patients, whereas door-to-groin time was much shorter in primary stroke center patients. Clinical Trial Registration:https://clinicaltrials.gov/ct2/show/NCT03356392 . Unique identifier NCT03356392